Under the never sky - Rossi, Veronica (Under the never sky trilogy, 2012)
Aria and Perry, two teens from radically different societies--one highly advanced, the other primitive--hate being dependent on one another until they overcome their prejudices and fall in love, knowing they can't stay together--Provided by publisher.